Patient-centeredness in physiotherapy: What does it entail? A systematic review of qualitative studies - Wijma, Amarins J; Bletterman, Anouck N; Clark, Jacqui R; Vervoort, Sigrid C.J.M; Beetsma, Anneke; Keizer, Doeke; Nijs, Jo; Van Wilgen, C. Paul (Physiotherapy theory and practice, 2017)
Purpose: The literature review is aimed at examining and summarizing themes related to patient-centeredness identified in qualitative research from the perspectives of patients and physiotherapists. Following the review, a secondary aim was to synthesize the themes to construct a proposed conceptual framework for utilization within physiotherapy. Methods: A systematic search of qualitative studies was conducted including all articles up to 2015 September. Methodological quality was examined with a checklist. The studies were examined for themes suggestive of the practice of patient centeredness from perspective of the therapists and/or the patients. Data were extracted using a data extraction form and analyzed following "thematic synthesis." Results: Fourteen articles were included. Methodological quality was high in five studies. Eight major descriptive themes and four subthemes (ST) were identified. The descriptive themes were: individuality (ST "Getting to know the patient" and ST "Individualized treatment"), education, communication (ST "Non-verbal communication"), goal setting, support (ST "Empowerment"), social characteristics of a patient-centered physiotherapist, a confident physiotherapist, and knowledge and skills of a patient-centered physiotherapist. Conclusions: Patient-centeredness in physiotherapy entails the characteristics of offering an individualized treatment, continuous communication (verbal and non-verbal), education during all aspects of treatment, working with patient-defined goals in a treatment in which the patient is supported and empowered with a physiotherapist having social skills, being confident and showing specific knowledge.